2016
DOI: 10.3390/ijerph13101023
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level, Multi-Component Approaches to Community Based Interventions for Healthy Living—A Three Case Comparison

Abstract: There is increasing interest in integrated and coordinated programs that intervene in multiple community settings/institutions at the same time and involve policy and system changes. The purpose of the paper is to analyse three comparable cases of Multi Level, Multi Component intervention programs (ML-MC) from across the world in order to give recommendations for research, policy and practice in this field. Through the comparison of three cases: Health and Local Community (SoL-program), Children’s Healthy Livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Given that resources are often limited, careful consideration of the strategies within any given MCI should be taken. In a review of three MCI case studies, Mikkelsen et al [37], found that using the full range of strategies are key to a successful implementation, and efforts to increase knowledge, enhance services, modify access, and change broader conditions should all be included. The HSHC MCIs included a variety of educational events/programs, as well as policy, practice, and environmental changes, but there were over three times more programs and events as compared to policy, practice, and environmental changes (1,703 vs. 471, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Given that resources are often limited, careful consideration of the strategies within any given MCI should be taken. In a review of three MCI case studies, Mikkelsen et al [37], found that using the full range of strategies are key to a successful implementation, and efforts to increase knowledge, enhance services, modify access, and change broader conditions should all be included. The HSHC MCIs included a variety of educational events/programs, as well as policy, practice, and environmental changes, but there were over three times more programs and events as compared to policy, practice, and environmental changes (1,703 vs. 471, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, formative research and/or adaptive intervention approaches should be conducted to understand how to influence product availability and placement within stores given previous evidence demonstrating the relationship between these dimensions and dietary behaviors [11,12,37,67]. One potential way to effectively manipulate multiple aspects of the in-store environment is by involving multiple partners [58,68]. For example, FV distributors and/or farmers could provide store owners/managers with technical assistance and training in acquiring and maintaining fresh FVs.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similar to ArCOPs experience, research has shown that involving key stakeholders in the planning and implementation of the intervention is essential for investment in the program, and is required for longterm program success and sustainability. 4,[13][14][15] Furthermore, the CDC also emphasizes the importance of local governments in creating physi- times (May to July) to discuss: opportunities for providing the community with health-related information; how to deliver the messages; how to brand the delivery; and development of a motto (eg, "Because you matter"). The Council decided to utilize the logo and information from a defunct website that was designed to address health issues and opportunities in the Policy, System and Environmental Approaches to Impact Obesity -Betancourt et al cal activity and food environments that promote health for their communities.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, there is increasing interest in programs that focus on changes at the environmental, system and policy levels. 4 In 2003, Arkansas became the first state in the United States to enact a law to create a comprehensive multipronged approach to bring families, schools and communities together to combat the epidemic of obesity. 5 From initial multilevel initiatives, the Arkansas Coalition for Obesity Prevention (ArCOP) was formed in 2007.…”
Section: Introductionmentioning
confidence: 99%